Labour Rights Violations in The Plastic Manufacturing Sector of Bogura Sadar Upazila: An Empirical Study of Factory Workers - Sumona Sharmin; Md Mahedi (Faculty of Law, Muhammadiyah University of Surabaya, 2024)
A significant number of workers are employed in Bangladesh’s plastic manufacturing sector. Although the Bangladesh Labour Act, 2006 establishes a comprehensive legal framework to protect workers’ rights, its implementation within the plastic industry remains inadequate. Consequently, plastic factory workers continue to experience widespread labour rights violations. This study aims to examine the nature, patterns, and underlying causes of labour rights violations affecting workers in the plastic manufacturing sector. Using a descriptive research design, primary data were collected from workers employed in plastic factories in Bogura Sadar, Bogura District. The findings indicate persistent violations, including low wages, excessive working hours, insufficient overtime compensation, gender-based discrimination, inhumane treatment, unhealthy and unhygienic working conditions, and inadequate occupational safety and security measures. The study concludes that weak law enforcement and ineffective monitoring mechanisms are the primary factors contributing to these violations. Therefore, strengthening the enforcement of the Bangladesh Labour Act, 2006 is essential to reducing labour rights violations and improving working conditions in Bangladesh’s plastic manufacturing sector.